Complexity and controversy in media coverage of Human papillomavirus (HPV) vaccination: A qualitative content analysis of news coverage in Denmark 2008–2018 - Agergaard, Torben E.; Smith, Màiri E.; Gammelby, Ane Kathrine; Tørring, Marie Louise; Nielsen, Kristian H. (Frontiers in Communication, 2023)
Traditional news media play an important, yet notoriously complex role in vaccination communication. News media remain a common source of information about vaccines and potentially influence individual decisions to choose vaccination or not. In Denmark, Human papillomavirus (HPV) vaccination rates remained relatively high until suspected adverse reactions began to receive extensive coverage in the news. Existing research studies associate the decline in HPV vaccination rates with misleading or negative news stories. We aimed to probe Danish media coverage beyond dichotomies such as misleading vs. informative, or negative vs. positive. We took a qualitative, contextual approach to media coverage of the Danish HPV vaccination crisis and recovery. Our research design focused on six national newspapers and 865 articles published in periods of peak media coverage from 2008 to 2018 (extracted from a total sample of 1,437 articles published between 1991 and 2019). We used qualitative content analysis to discern the main topics covered, and we analyzed contextual factors that affected the meanings of main topics. Our results confirm the rise of suspected adverse reactions as the dominant main topic in 2015. However, we find that news stories about adverse reactions were diverse and closely related to other main topics such as conflicts of interests and debate among experts and other stakeholders. In 2017, the media began downplaying suspected adverse events when concerns about declining vaccination rates and misinformation by the media were voiced. Our findings suggest that controversial media messages about vaccination are hard to classify as either negative or positive but must be interpreted carefully in context of what is known about the controversy. Learning from past media controversies remains important to understanding the media’s role in the social construction of risks and benefits associated with vaccination.